Application and prospects of robotic surgery in children: a scoping review. Issue 4 (31st October 2022) - Shen, Lei Ting; Tou, Jinfa
Abstract : As an innovative minimally invasive surgical technology, robot-assisted surgery (RAS) has greatly improved the accuracy and safety of surgery through the advantages of three-dimensional magnification, tremor filtering, precision and flexibility, and has been carried out by an increasing number of surgeries. In recent years, robots have been gradually applied to children, bringing new ideas and challenges to pediatric surgeons. This review will describe the advantages and limitations of robotic surgery in children, summarize its application in pediatric surgery, and provide an outlook. It is believed that clinicians should actively carry out RAS under the premise of rigorously ensuring surgical indications and strive to improve the efficacy of surgical treatment for children.